2012
DOI: 10.1051/0004-6361/201220203
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic diffusion of Galactic cosmic ray protons and their steady-state azimuthal distribution

Abstract: Galactic transport models for cosmic rays involve the diffusive motion of these particles in the interstellar medium. Owing to the large-scale structured Galactic magnetic field, this diffusion is anisotropic with respect to the local field direction. We included this transport effect along with continuous loss processes in a quantitative model of Galactic propagation for cosmic ray protons that is based on stochastic differential equations. We calculated energy spectra at different positions along the Sun's G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 64 publications
(83 reference statements)
6
53
0
Order By: Relevance
“…In addition, anisotropic diffusion is also seen to be essential for CR-driven magnetic dynamo action in galaxies (Hanasz et al 2009). Including a moderate anisotropy for diffusion has given more consistent results with recent estimates of the local interstellar proton spectrum compared to normal isotropic diffusion (Effenberger et al 2012). As this model has only one spatial dimension, we only implement a one-halo model.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, anisotropic diffusion is also seen to be essential for CR-driven magnetic dynamo action in galaxies (Hanasz et al 2009). Including a moderate anisotropy for diffusion has given more consistent results with recent estimates of the local interstellar proton spectrum compared to normal isotropic diffusion (Effenberger et al 2012). As this model has only one spatial dimension, we only implement a one-halo model.…”
Section: Discussionsupporting
confidence: 68%
“…In particular, for a given realization of galactic source spatial distribution, the dipole anisotropy would point toward the source with the largest contribution (Erlykin & Wolfendale 2006;Blasi & Amato 2012;Ptuskin 2012;Pohl & Eichler 2013;Sveshnikova et al 2013;Savchenko et al 2015), which may change with energy, in agreement with observations. On the other hand, the systematic overestimation of the anisotropy amplitude may be partially compensated by the fact that diffusion is expected to be anisotropic (see, e.g., Effenberger et al 2012), thus modifying the expected cosmic-ray density gradient shape as a function of the source direction with respect to the regular galactic magnetic field (Kumar & Eichler 2014). The misalignment between the cosmic-ray density gradient and the regular galactic magnetic field would prevent pointing to any specific source, and it would suppress the anisotropy amplitude to a value closer to what has been observed (Mertsch & Funk 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These need to be taken into account whenever the predominant direction of spatial diffusion does not coincide with the directions of the numerical grid. Effects of such an anisotropic diffusion tensor have already been studied previously in the context of spiral-arm cosmic-ray source distributions (see [6]), where the authors showed a significant impact of such an anisotropic diffusion tensor. Apart from that [9] used spatially variable diffusion as an alternative explanation to the cosmic-ray gradient problem.…”
Section: Propagation Physicsmentioning
confidence: 82%
“…The impact of spiral-arm source distributions on the different cosmic ray observables has been studied recently by several groups including [3,6,10,13] and [26]. Results obtained for such a study for the highest resolution so far done with PICARD are shown in Fig.…”
Section: Pos(icrc2015)554mentioning
confidence: 99%